Coordination models and Languages : 19th IFIP WG 6.1 International Conference, COORDINATION 2017, held as part of the 12th International Federated Conference on Distributed Computing Techniques, DisCoTec 2017, Neuchâtel, Switzerland, June 19-22, 2017, Proceedings /: 19th IFIP WG 6.1 International Conference, COORDINATION 2017, held as part of the 12th International Federated Conference on Distributed Computing Techniques, DisCoTec 2017, Neuchâtel, Switzerland, June 19-22, 2017, Proceedings. (2017) - Unknown
No abstract available